Pathogenic microRNA’s in myeloid malignancies - Khalaj, Mona; Tavakkoli, Montreh; Stranahan, Alec W.; Park, Christopher Y. (Frontiers in Genetics, 2014)
Recent studies have significantly improved our understanding of the microRNA (miRNA) roles in regulating normal hematopoiesis, including their function in hematopoietic stem cells (HSCs). Since miRNAs are critical for maintaining HSCs as well as the development of their mature progeny, it is not surprising that miRNAs also serve oncogenic and tumor suppressive roles in hematologic malignancies including acute myeloid leukemia (AML) and the myelodysplastic syndromes (MDS). A number of studies have extensively documented the widespread dysregulation of miRNA expression in human AML, and these results have inspired numerous investigations exploring the functional roles of miRNAs in myeloid leukemogenesis. While these studies have revealed that the number of miRNAs exhibiting altered expression in AML is large, only a small number of miRNAs have been confirmed as regulators of the AML development or maintenance. Herein, we summarize the miRNA’s for which strong experimental evidence supports their functional roles in AML and/or MDS pathogenesis. We also discuss the implications of these studies, including how they may aid in identifying new miRNA-mediated therapeutic targets for these diseases.